The Category of Unauthorized Donations Via Tiktok is Included as an Act of Begging in Article 504 of the KUHP - Oky Putri Firninda; Emmilia Rusdiana (NOVUM : JURNAL HUKUM, 2025)
The development of the times and technology does have a good impact, but it often also creates new problems. One of them is begging that is conducted online. The rules of begging already exist in the Criminal Law and also in several Regional Regulations. However, these regulations do not specifically mention the definition of begging carried out in networks. Begging that is carried out online, so this research raises legal issues of norm ambiguity. The purpose of this research is to find out whether Surabaya Regional Regulation has regulated begging that is carried out in networks. Then it will be examined whether this begging in the network can be subject to Article 504 of the Criminal Code on begging in public or not. The method used in this research is normative juridical. The results of the discussion show that, being in the network can be equated with begging that is often can be equated with begging that we often encounter in public places. So that Article 504 of the Criminal Code can be used to sanction someone who is begging in the network.